2009
DOI: 10.1002/pros.20975
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast inhibits hormone refractory prostate cancer cell proliferation and suppresses transforming growth factor β1‐associated osteoblastic changes

Abstract: These observations suggest that tranilast may be a useful therapeutic agent for treatment of HRPC via the direct inhibitory effect on cancer cells and suppression of TGF-beta1-associated osteoblastic changes in bone metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 38 publications
3
44
1
Order By: Relevance
“…So, we inferred that OS pathogenesis may be related to wnt and Myc pathway abnormality and the genes in these functional nodes, such This result agreed with the findings of previous studies: TGFB1 involves in the osteoblastic changes in bone metastasis [19], and the differentiation of cancer cells to cancer stem cells in OS [20]; FLT3 could inhibit proliferation and promote cell death in OS cell lines [21]. Moreover, the metastatic and non-metastatic OS are closely related to KDM1A gene down-regulation, which is an evidence supporting the points that KDM1A is a therapeutic target for OS [22] and KRAS is a underlying target gene for OS treatment [23].…”
Section: Discussionsupporting
confidence: 91%
“…So, we inferred that OS pathogenesis may be related to wnt and Myc pathway abnormality and the genes in these functional nodes, such This result agreed with the findings of previous studies: TGFB1 involves in the osteoblastic changes in bone metastasis [19], and the differentiation of cancer cells to cancer stem cells in OS [20]; FLT3 could inhibit proliferation and promote cell death in OS cell lines [21]. Moreover, the metastatic and non-metastatic OS are closely related to KDM1A gene down-regulation, which is an evidence supporting the points that KDM1A is a therapeutic target for OS [22] and KRAS is a underlying target gene for OS treatment [23].…”
Section: Discussionsupporting
confidence: 91%
“…In a co-culture human scirrhous gastric cancer cell line, OCUM-2M with fibroblasts, which produce TGF-␤1, invasiveness, increased significantly and this effect was countered by tranilast [165]. In prostate cancer cells, this drug suppressed the secretion of TGF-␤1 from bone-derived stromal cells and inhibited TGF-␤1-associated differentiation of these cells [86].…”
Section: Tranilast and Tgf-ˇ Signalingmentioning
confidence: 95%
“…Tranilast also suppressed the secretion of TGF-␤1 from bone-derived stromal cells, and inhibited TGF-␤1-associated differentiation of bone-derived stromal cells and osteoblastic changes [86]. To verify its clinical effect, in a pilot study by Izumi et al, tranilast exhibited benefit in the treatment and prognosis for patients with advanced castration-resistant prostate cancer (CRPC).…”
Section: Prostate Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, it was reported the ability of TN to downregulate TGF-beta production from bone stromal cells and other different cell types, thereby suppressing TGF- β -stimulated osteoclast differentiation which underlies, in part, osteoblastic bone metastasis [61, 166]. Noguchi et al [62] demonstrated that three weeks of TN treatment significantly reduced the tumor growth and metastasis, when administered daily by intraperitoneal injection (4 mg/animal), in a mouse model of oral squamous cell carcinoma.…”
Section: Potential Role Of Mast Cells Tryptase Inhibitors In Cancermentioning
confidence: 99%